O ensino de Botânica: contribuições de uma sequência didática fundamentada em documentos normativos educacionais e na perspectiva histórico-cultural - Gonzalez Bisneto, Mauricio (2024)
In this work, our objective was to develop and evaluate the contributions of a Didactic Sequence (DS), based on a Historical-Cultural perspective of Human Development, drawing on the ideas of Vygotsky, for the teaching and learning process of skills and knowledge objects that may be related to the content of Botany, as outlined in the National Common Core Curriculum (BNCC) and the Curriculum of Reference of Mato Grosso do Sul - High School Level (CRMSEM). The DS consists of three stages: identification of the knowledge already appropriated by the students, systematization of knowledge, and evaluation of conceptual evolution. This DS was developed in a first-year High School class of a public school, located in the municipality of Campo Grande - MS. Drawings, analysis, and artistic productions were carried out by the students to identify and/or evaluate the appropriated knowledge. These data were collected through activity submissions, as well as general aspects of their development and non-verbal interactions, which were recorded in a logbook by the teacher/researcher. Furthermore, all activities of the DS were recorded using a voice recording app, allowing us to register the dialogues and interactions between the students and the teacher-researcher, which were later transcribed. Subsequently, the data obtained were evaluated using a Microgenetic Analysis approach. The results of this research demonstrated that the activities of the DS can promote conceptual evolution and knowledge appropriation, thus contributing to the teaching and learning process of skills and knowledge objects outlined in the BNCC and the Curriculum of Reference of Mato Grosso do Sul - High School Level, related to Botany content. Additionally, the DS can serve as a tool to mitigate the so-called 'botanical blindness' and provide teachers with a methodological framework to guide their pedagogical practices in this new educational curricular reality.